Maximizing Corporate Value through Mergers and Acquisitions : a Strategic Growth Guide. - Gaughan, Patrick A. (Wiley finance series., 2013)
Solid guidance for selecting the correct strategic basis for mergers and acquisitions Examining how M & A fits in corporate growth strategies, Maximizing Corporate Value through Mergers and Acquisitions covers the various strategic reasons for companies entering mergers and acquisitions (M & A), with a look at those that are based on sound strategy, and those that are not. Helps companies decide whether M & As should be used for growth and increased corporate valueExplores why M & A deals often fail to deliver what their proponents have represented they wouldEx.